THE INFLUENCE OF FACILITIES ON CUSTOMER SATISFACTION IN SHANTUNG 77 KUOTIE KELAPA GADING - Sofiani Sofiani (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2021)
The city of Jakarta is one that has a wide variety of culinary and food products for sale, very tight competitors among food entrepreneurs vying for greater consumer trust. One of the things contained in consumer trust is a facility that can meet customer satisfaction at a place to eat. This study aims to determine the effect of facilities on customer satisfaction in Shantung 77 Kuotie Kelapa GadingThe results showed that in the t test, it was known that the sig value for the effect of Facilities (X) on Customer Satisfaction (Y) can be concluded that the Facility variable is rejected, which means that there is a significant influence of facilities on customer satisfaction. Suggestions for Shantung 77 Kuotie Kelapa Gading to improve facilities so that there are no complaints from customers and make customers at Shantung 77 Kuotie Kelapa Gading satisfied with the existing facilities and location. For Shantung 77 Kuotie Mangga Besar to always maintain existing facilities so that there are no complaints from customers.